Pendampingan Produk UMKM Olahan Talas Melalui Bazar untuk Meningkatkan Pendapatan di Kelurahan Panaragan Kota Bogor - Wulandari, Siswi; Gayatri, Askardiya Mirza; Oktaviana, Rully Noor; Mulyani, Deta; Prameswari, Shinta Kania (Abdimas Universal, 2026)
One of the programs initiated by the Bogor City Department of Housing and Settlement is the Bogor Slum-Free Movement for the Acceleration Strategy of Beautiful, Healthy, Safe, and Comfortable Settlements, abbreviated as Gerobak Sae Pisan, which aims to boost the people's economy, MSMEs, and community empowerment. The pilot project for the implementation of Gerobak Sae Pisan is located in Mantarena Lebak RW 02, Panaragan Village. The implementation of this community service activity is a follow-up to previous activities, namely providing assistance in producing various taro-based products. Using a participatory approach method through intensive motivation with a personal and small group approach, the issue was found that partners lack confidence both in making products and in marketing. Therefore, intensive mentoring is required to prepare them to venture into the culinary business, in this case through bazaar activities as a means of self-actualization, so that the products are better known to the wider community and to increase income. Featured products made from taro are still being developed in Mantarena, Panaragan Village, Bogor, where so far no other area has developed them. Bazaar activities are an effort to introduce featured taro-based products and increase MSMEs' income.